BSA-Assisted Synthesis of Au Nanoclusters/MnO2 Nanosheets for Fluorescence “Switch-On” Detection of Alkaline Phosphatase - Yijiong Xue; Chengqi Bao; Hui Liu; Fanghui Ma; Minghui Yang; Xiaoqing Li (Biosensors)
A fluorescence probe for “switch-on” detection of alkaline phosphatase (ALP) was developed based on Au nanoclusters anchored MnO2 nanosheets (Au NCs-MnO2 NSs), which were synthesized using bovine serum albumin (BSA) as template through a simple one-pot approach. In the sensing system, MnO2 NSs function as both energy acceptors and target identifiers, effectively quenches the fluorescence of Au NCs via fluorescence resonance energy transfer (FRET). The presence of ALP catalyzes the hydrolysis of L-ascorbic acid-2-phosphate (AAP) to ascorbic acid (AA), reducing MnO2 NSs to Mn2+ and facilitate the fluorescence recovery of Au NCs. The fluorescence assay offers the advantages of facile preparation, cost-effectiveness, good specificity, and high sensitivity. Moreover, the assay exhibits a broad linear range (0.005 U/mL to 8 U/mL) for ALP detection with a remarkable limit of detection of 0.0015 U/mL. Notably, this assay demonstrates promising applicability for detection ALP in human serum samples, thereby providing valuable potential for clinical applications.